Molasses fermentation to ethanol by SaccharomycescerevisiaeM30 using low ultrasonic frequency stimulation - Klomklieng, Wannaphop; Prateepasen, Asa (Asia-Pacific Journal of Science and Technology, 2017)
The effect of low-frequency ultrasonic power (20-30 kHz) on ethanol production from molasses by Saccharomycescerevisiae M30 at 30-35°C was studied. Ultrasonic power was continuously supplied to the fermentation systems. Fermentation environment and process performance were evaluated during bioreactor operation. The bioreactor operation with supplying of 20-25 kHz of ultrasonic power could perform under normal pH (4.6-5.0) and liquid temperature (≤ 38°C), while at 30 kHz a high liquid temperature (≤ 40°C) wascreated. Thus, the ultrasonic power at 30 kHz affected to yeast activity in this bioreactor. Models of specific ethanol production rate (v) and specific ethanol production time (T) were used to evaluate the efficiency of ultrasonic power in enhancing ethanol production. The results confirmed that ultrasonic power could enhance the ethanol production by enhancing yeast activity. The optimum ultrasonic frequency to stimulate the fermentation system was achieved at 25 kHz. Under this condition, the maximum v and T were obtained at 1.55 and 1.9 g/g.h, respectively